Gene Therapy for the Heart Lessons Learned and Future Perspectives. Issue 10 (8th May 2020) - Cannatà, Antonio; Ali, Hashim; Sinagra, Gianfranco; Giacca, Mauro
Abstract : While clinical gene therapy celebrates its first successes, with several products already approved for clinical use and several hundreds in the final stages of the clinical approval pipeline, there is not a single gene therapy approach that has worked for the heart. Here, we review the past experience gained in the several cardiac gene therapy clinical trials that had the goal of inducing therapeutic angiogenesis in the ischemic heart and in the attempts at modulating cardiac function in heart failure. Critical assessment of the results so far achieved indicates that the efficiency of cardiac gene delivery remains a major hurdle preventing success but also that improvements need to be sought in establishing more reliable large animal models, choosing more effective therapeutic genes, better designing clinical trials, and more deeply understanding cardiac biology. We also emphasize a few areas of cardiac gene therapy development that hold great promise for the future. In particular, the transition from gene addition studies using protein-coding cDNAs to the modulation of gene expression using small RNA therapeutics and the improvement of precise gene editing now pave the way to applications such as cardiac regeneration after myocardial infarction and gene correction for inherited cardiomyopathies that were unapproachable until a decade ago.